Validation of Dive Foraging Indices Using Archived and Transmitted Acceleration Data: The Case of the Weddell Seal - Heerah, Karine; Cox, Sam L.; Blevin, Pierre; Guinet, Christophe; Charrassin, Jean-Benoît (Frontiers in Ecology and Evolution, 2019)
Dive data collected from archival and satellite tags can provide valuable information on foraging activity via the characterisation of movement patterns (e.g. wiggles, hunting time). However, a lack of validation limits interpretation of what these metrics truly represent in terms of behaviour and how predators interact with prey. Head-mounted accelerometers have proven to be effective for detecting prey catch attempt (PrCA) behaviours, and thus can provide a more direct measure of foraging activity. However, device retrieval is typically required to access the high-resolution data they record, restricting use to animals returning to predictable locations. In this study, we present and validate data obtained from newly developed satellite-relay data tags, capable of remotely transmitting summaries of tri-axial accelerometer measurements. We then use these summaries to assess foraging metrics generated from dive data only. Tags were deployed on four female Weddell seals in November 2014 at Dumont d’Urville, and successfully acquired data over ~two months. Retrieved archival data for one individual, and transmitted data for four individuals were used to (1) compare and validate abstracted accelerometer transmissions against outputs from established processing procedures, and (2) assess the validity of previously developed dive foraging indices, calculated solely from time-depth measurements. We found transmitted estimates of PrCA behaviours were generally comparable to those obtained from archival processing, although a small but consistent positive bias was noted. Following this, dive foraging segments were identified either from (1) sinuosity in the trajectories of high-resolution depth archives, or (2) vertical speeds between low resolution transmissions of key depth inflection points along a dive profile. In both cases, more than 93% of the estimated PrCA behaviours (from either abstracted transmissions or archival processing) fell into inferred dive foraging segments (i.e. « hunting » segments), suggesting the two methods provide a reliable indicator of foraging effort. The validation of transmitted acceleration data and foraging indices derived from time-depth recordings for Weddell seals offers new avenues for the study of foraging activity and dive energetics. This is especially pertinent for species from which tag retrieval is challenging, but also for the post-processing of the numerous low-resolution dive datasets already available.